"Double-Bubble" Descemet Membrane Endothelial Keratoplasty Unfolding in Eyes With Deep Anterior Chambers and Anterior Chamber Intraocular Lenses. Issue 7 (July 2020) - Parker, Jack S.; Parker, John S.; Melles, Gerrit R.J.
Abstract : Purpose: To describe a standardized technique for Descemet membrane endothelial keratoplasty unfolding in eyes with deep anterior chambers and anterior chamber intraocular lenses (ACIOLs). Methods: Two air bubbles are used simultaneously: the first placed on top of the graft and the second one underneath. Results: The 2 bubbles work in concert—the bubble on top props the tissue partially open, while the bubble underneath levitates the graft away from the ACIOL and provides support for subsequent unfolding maneuvers. Conclusions: By sandwiching the graft between 2 bubbles, unfolding may proceed away from physical contact with the ACIOL, even in eyes with hyper-deep chambers.